Percutaneous ultrasound-guided balloon-assisted embolization of iatrogenic femoral artery pseudoaneurysms with Glubran®2 cyanoacrylate glue: safety, efficacy and outcomes - Griviau, Loïc; Chevallier, Olivier; Marcelin, Clément; Nakai, Motoki; Pescatori, Lorenzo; Galland, Christophe; Midulla, Marco; Falvo, Nicolas; Loffroy, Romaric (Quantitative Imaging in Medicine and Surgery, 2018)
Background: Femoral pseudoaneurysm (PA) is a frequent complication of arterial access for endovascular procedures. Surgery has traditionally been considered as the gold standard of therapy. We aimed to report our experience of percutaneous ultrasound (US)-guided balloon-assisted embolization with cyanoacrylate glue for the treatment of iatrogenic femoral PAs. Methods: Retrospective two-center study of patients with femoral iatrogenic PAs treated by N-butyl cyanoacrylate-methacryloxy sulfolane (NBCA-MS) Glubran®2 glue embolization between July 2013 and November 2017. All patients underwent contralateral arterial access with balloon placement of an appropriate size in front of the PA neck before glue/lipiodol embolization in a 1:1 ratio by percutaneous US-guided puncture of the aneurysmal sac under fluoroscopy control. Results: Twenty-three patients (12 females, 11 males; median age, 79 years; range, 18–93 years) were included. Median PA size was 34 mm (range, 17–60 mm). The median time to treatment was 5 days (range, 1–30 days). Twenty patients (86.9%) were successfully treated by glue injection alone. The three remaining patients (13.1%) with persistent PA or associated arterial-venous fistula were immediately treated during the same procedure by additional stent-graft. Then, overall immediate and 1-month clinical success rates were 100%. No surgical conversion was necessary. No recurrence was reported during the median follow-up of 11 months (range, 2–73 months). Two (8.7%) puncture-related complications occurred at the contralateral arterial access site, which spontaneously resolved. No non-target glue embolization occurred. Conclusions: US-guided balloon-assisted glue embolization is safe and effective to treat iatrogenic femoral PAs in most cases, offering complete exclusion of the PA and avoiding the morbidity of open surgery.